2001
DOI: 10.1097/00000539-200104000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Voluven®, a Lower Substituted Novel Hydroxyethyl Starch (HES 130/0.4), Causes Fewer Effects on Coagulation in Major Orthopedic Surgery than HES 200/0.5

Abstract: Hydroxyethyl starches are common plasma volume expanders, but may interfere with coagulation at large doses. We tested a novel hydroxyethyl starch specification (Voluven; Fresenius Kabi, Bad Homburg, Germany) which was developed to reduce hemostatic interactions while preserving its efficacy in restoring plasma volume in comparison to HAES-steril (pentastarch; Fresenius Kabi) in major orthopedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
2
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(106 citation statements)
references
References 20 publications
6
90
2
8
Order By: Relevance
“…The hemodilution effect of HES 130/0.4 associated with its mode of action was reflected by significant changes in hematological and coagulation parameters. The quick recovery of Factor VIII and vWF in adults after surgery is in line with other findings [3,11,12]. However, it is not possible to separate the effects of profound bleeding from those attributable to hemodilution in an uncontrolled trial.…”
Section: In Patients Undergoingsupporting
confidence: 78%
See 1 more Smart Citation
“…The hemodilution effect of HES 130/0.4 associated with its mode of action was reflected by significant changes in hematological and coagulation parameters. The quick recovery of Factor VIII and vWF in adults after surgery is in line with other findings [3,11,12]. However, it is not possible to separate the effects of profound bleeding from those attributable to hemodilution in an uncontrolled trial.…”
Section: In Patients Undergoingsupporting
confidence: 78%
“…They concluded that the hemodynamic effects of 6% HES 130/0.4 were at least similar to 5% human albumin. Langeron et al (2001) [11] and Gandhi et al (2007) [12] could demonstrate equivalence of 6% HES 130/0.4 with 6% HES 200/0.5 or 6% HES 450/0.7 in volume needed to restore or maintain hemodynamics during orthopedic surgery. Vogt et al (1996) [13] compared 6% HES 200/0.5 with 5% human albumin and demonstrated similar volume needs to stabilize hemodynamics.…”
Section: In Patients Undergoingmentioning
confidence: 97%
“…Therefore, HES solutions with lower MW and a lower degree of substitution have been developed (i.e., HES 130/0.4). The coagulation disturbances caused by modern HES solutions do not seem to be related to increased postoperative bleeding after various types of major surgery (Langeron et al 2001, Kozek-Langenecker et al 2008. The present study demonstrated that the effects of HES and gelatin solutions on blood loss are similar.…”
Section: Colloids and Crystalloids After Cardiac Surgery: Coagulationsupporting
confidence: 46%
“…The first reports of negative effects of high-MW HES solutions on blood coagulation were published in 1965 (Thompson and Gadsden). The possible mechanisms have been widely studied in experimental (Hiippala 1995, Nielsen 2005 and clinical studies (Langeron et al 2001, Boldt et al 2002. Large HES molecules interfere with fibrinogen, coagulation factor VIII, and von Willebrand factor, and their negligible effect on coagulation is more than can be expected as a result of hemodilution (Omar et al 1999).…”
Section: Coagulation Effects Of Hydroxyethyl Starchesmentioning
confidence: 99%
“…In general, an HES solution with low molecular weight (MW) and low degree of substitution (DS) is preferred because HES solution with high MW and high DS is harder to metabolise or eliminate and thus has a prolonged adverse effect on coagulation [2,[6][7][8][9][10][11][12]. Recently, several studies of balanced salt-based HES solution with high MW and high DS (670 ⁄ 0.75; referred to as bhHES hereafter) have reported beneficial effects on coagulation [13][14][15].…”
mentioning
confidence: 99%